Cardiomyopathy induced by anabolic-androgenic steroid abuse. (23rd July 2018) - Garner, Orlando; Iardino, Alfredo; Ramirez, Ana; Yakoby, Maty
Abstract : Bodybuilders use anabolic-androgenic steroids to increase muscle mass, but abuse of these hormones has been related to cardiomyopathy in the past. A 60-year-old Caucasian male bodybuilder with medical history of male hypogonadism and on testosterone replacement therapy, allegedly preparing for a weightlifting competition and receiving stem cell infusions from his trainer, is transferred to the intensive care unit for worsening shortness of breath after failing treatment for community-acquired pneumonia. Chest X-ray on transfer was suggestive of pulmonary oedema, and transthoracic echocardiography showed an ejection fraction of 25%–30%. The patient was taken for cardiac catheterisation, which yielded non-ischaemic cardiomyopathy. His testosterone levels were supratherapeutic. Anabolic-androgenic steroid abuse can be a cause of cardiomyopathy in patients who have no other risk factor for such disease.